Musculoskeletal Ultrasound in Orthopedic and Rheumatic disease in Adults - Martino, Fabio; Silvestri, Enzo.; Orlandi, Davide; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the major advances and technological updates in diagnostic ultrasound procedures, focusing on the principal technological aspects and multiple exam procedures for the pertinent anatomy, both under basal conditions and using Doppler techniques. It offers a comprehensive and precise evaluation of the ultrasound semiotics of the musculoskeletal apparatus, with descriptions of numerous rheumatic and orthopedic disease patterns. It also discusses in detail the vital role of ultrasound in monitoring chronic inflammatory joint disease during therapy, and brand-new highly sensitive Doppler techniques. In view of the tremendous impact of ultrasound-guided interventional procedures on the management of drug delivery in a musculoskeletal setting, the book also includes a chapter on the practical aspects of performing US-guided diagnostic and therapeutic procedures. Providing outstanding diagrams, dynamic images and videos to guide readers, it is a valuable resource for radiologists and clinicians (rheumatologists, orthopedists, physiatrists and anesthesiologists) with different levels of experience $1 (Branging from physicians in training to those who already perform US examinations and US-guided procedures.s
1. Osseous and cartilagineous surface -- 2. Synovial spaces -- 3. Tendons and ligaments -- 4. Muscles -- 5. Peripheral nerves -- 6. Dermis and Hypodermis -- 7. Osteoarthritis -- 8. Rheumatoid arthritis -- 9. Seronegative spondyloarthritis.-10. Crystal-related arthropathies -- 11. Connective tissue disorders -- 12. Metabolic diseases -- 13. Synovial osteochondromatosis -- 14. Pigmented villonodular synovitis -- 15. Shoulder calcific tendinitis -- 16 Frozen shoulder -- 17. Septic arthritis -- 18. Hemophiliac arthropathy,- 19. Bone trauma -- 20. Muscle injury -- 21. Tendon -- 22. Superficial interosseous ligament injury -- 23. Peripheral entrapment neuropathies -- 24. Bone fracture healing -- 25. Tendon and muscle rupture repair -- 26. Therapy efficacy evaluation in synovitis -- 27. Introduction -- 28. Joint and bursal infiltration -- 29. Tendon infiltrative and regenerative treatments -- 30. Calcific tendinitis treatment -- 31. Peripheral nerve block -- 32. Fluid collection evacuation.
Keywords: Radiology; Rheumatology; Orthopedics; Radiology; Rheumatology; Orthopaedics; Musculoskeletal System -- diagnostic imaging; Musculoskeletal Abnormalities; Musculoskeletal System; Rheumatic Diseases; Orthopedics